STRATEGI PEMASARAN PRODUK HERBALIFE (STUDI KASUS RUMAH NUTRISI GREEN) - Gleyni ., Supit; Ribka M. Kumaat; Agnes E. Loho (Sam Ratulangi University, 2016)
This study aims to determine the marketing strategy Herbalife in Manado City. The method of determining the area of research done in purposive, using the case study method which is a description of a real-life experience, which is used to make points, raise issues or otherwise enhance understanding and learning experience of the participants. Where, Nutrition Green House as a location or point of research. Data analysis method used is descriptive analysis, SWOT analysis, and business strategy theory. The results showed that the strategies that have been applied are maintained and add to the marketing strategy of